Effects of wet-dry-freeze-thaw cycles on the response of the frozen soil-composite geotextile interface in direct shear tests - Pengfei He; Haitao Cao; Jianhua Dong; Guangliang Hou; Yanhu Mu; Jicun Zhang (Case Studies in Thermal Engineering)
Composite geotextiles are frequently utilized in water delivery canals and other projects in cold regions. However, the peak strength of the soil-geotextile interface can be degrade due to continuous wet-dry-freeze-thaw (WDFT) cycles, potentially compromising the stability of the infrastructure. This paper presents the use of a temperature-controlled direct shear system to conduct direct shear tests on the interface between the soil and the geotextile composite under a variety of normal pressures, temperatures, and WDFT cycles. The study shows that WDFT has minimal effect on the shear stress-shear displacement curve at positive temperatures. At negative temperatures, the curve transitions from strain hardening to strain softening. At negative temperatures, the average increase in peak strength was 39 %, 56.9 %, and 65.3 % after a single WDFT cycle at −2 °C, −6 °C, and −10 °C, respectively. A gradual decline in peak strength was observed with each subsequent cycle, although the peak strength remained slightly higher than the initial strength. The average growth rates were 6.6 %, 19.3 %, and 29.2 % after ten cycles, respectively. The interfacial cohesion and friction angle exhibited similar trends to those of peak strength. The sensitivity analysis revealed that temperature and WDFT cycles exert a considerable influence on the interface cohesion.